Ready or Not—Here They Come! - Lachance, Laurie (Maine Policy Review, 2003)
Laurie Lachance, Maine’s state economist, outlines the economic implications of the “tidal wave” of aging baby boomers that will shortly be hitting Maine, and what might be done to prepare for it. She asks whether Maine has appropriate housing, transportation, and health care services to care for the needs of an aging population, and how Maine will fund the needed infrastructure with a smaller labor force. Lachance notes that there is still time to prepare. Seniors are and will be living longer, healthier lives; they are and will be increasingly engaged in social, cultural and educational activities; this and future generations of seniors will have greater financial resources than seniors of the past. In addition, a new group of relatively wealthy, early retirees are choosing Maine as a retirement destination. Future growth of the retirement industry in Maine may become somewhat of a positive economic force, as the boomers seek a safe, clean retirement location with opportunities for an active lifestyle.
Keywords: Maine demographics; aging